2014
DOI: 10.1016/j.atmosenv.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal characteristics of biogenic and anthropogenic isoprene in tropical–subtropical urban environments

Abstract: h i g h l i g h t sIsoprene in urban environments at tropicalesubtropical latitudes was studied. Seasonal and spatial differences in isoprene's levels and sources were investigated. A temperature kick-start threshold of isoprene emissions was clearly demonstrated. Such a threshold may vary with vegetation types and temperature zones. a b s t r a c tMeasurements of atmospheric isoprene and other selected volatile organic compounds (VOCs) were conducted in Taipei, a tropicalesubtropical metropolis, to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 46 publications
2
24
0
1
Order By: Relevance
“…Two-year worth of data from 2008 to 2010 for the Wanhua site were used for the study, which included approximately 5 × 10 5 data points. This highly temporally resolved dataset from a fixed site revealing very detailed features in variations of the PAMS species, including isoprene and ethylene, is hardly achievable by the flask sampling method (Wang et al, 2013;Chang et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two-year worth of data from 2008 to 2010 for the Wanhua site were used for the study, which included approximately 5 × 10 5 data points. This highly temporally resolved dataset from a fixed site revealing very detailed features in variations of the PAMS species, including isoprene and ethylene, is hardly achievable by the flask sampling method (Wang et al, 2013;Chang et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Isoprene is a C 5 compound listed as one of the 54 PAMS species analyzed on the hourly basis by the PAMS network. Although 1, 3-butadiene was commonly used as the indicator of vehicular emissions in an urban setting to separate the contributions of biogenic vs anthropogenic sources (Reimann et al, 2000;Borbon et al, 2001;Wang et al, 2013;Chang et al, 2014), it was not targeted by the PAMS list of the 54 target compounds. Instead, ethylene was used as the surrogate of vehicular source (McLaren et al, 1996;Reimann et al, 2000;Borbon et al, 2001) (See Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the strong anthropogenic pollutant emissions in East Asia (China, Japan, and South Korea), recent research has shown that isoprene accounts for a major OH chemical sink in suburban areas near Beijing (Ran et al, 2011), the Pearl River Delta region , Taipei (Chang et al, 2014), and Seoul (Kim et al, 2013b;Kim et al, 2013). Consequently, modeling studies also clearly show that isoprene contributes significantly to ozone formation in Asian megacity regions.…”
mentioning
confidence: 97%